206k views
2 votes
Given the equation p=s1t-s2t, which equation is solved for t?

A. t=p(s1-s2)

B. t=p-s1+s2

C. t=p/s1-s2

D. t=p/s1+s2

2 Answers

1 vote

Answer:it’s b

Explanation:

User Kremena
by
5.3k points
2 votes

Answer:


t=(p)/((s_1-s_2))

Therefore, C is the correct option.

Explanation:

We have been given the equation
p=s_1t-s_2t

The GCF of the right hand side of the equation is t. Hence, factored out the GCF.


p=(s_1-s_2)t

Now,
(s_1-s_2 is in multiplication with 't'. So in order to isolate t, we can divide both sides by
(s_1-s_2)


t=(p)/((s_1-s_2))

Therefore, C is the correct option.

User Starasia
by
4.3k points